Roles of Reactive Oxygen Species and Mitochondria in Seed Germination - Farooq, Muhammad Awais; Zhang, Xiaomeng; Zafar, Muhammad Mubashar; Ma, Wei; Zhao, Jianjun (Frontiers in Plant Science, 2021)
Seed germination is crucial for the life cycle of plants and maximum crop production. This critical developmental step is regulated by diverse endogenous (hormones, reactive oxygen species (ROS) and exogenous (light, temperature) factors. ROS promote the release of seed dormancy by biomolecules oxidation, testa weakening and endosperm decay. ROS modulate metabolic and hormone signaling pathways that induce and maintain seed dormancy and germination. Endosperm provides nutrients and senses environmental signals to regulate the growth of the embryo by secreting timely signals. The growing energy demand of the developing embryo and endosperm is fulfilled by functional mitochondria. Mitochondrial matrix-localized heat shock protein GhHSP24.7 controls seed germination in a temperature-dependent manner. In this review, we summarize comprehensive view of biochemical and molecular mechanisms, which coordinately control seed germination. We also discuss that the accurate and optimized coordination of ROS, mitochondria, heat shock proteins is required to permit testa rupture and subsequent germination.